Detection of highly potent Stx2a-encoding gene in pig fecal DNA in Serbia: Could commercial pig farms in Serbia act as source of human STEC infections? - Vračar, V; Mitrović, J; Lalošević, V; Kozoderović, G; Petrovic, D (Journal of the Hellenic Veterinary Medical Society, 2025)
Shiga toxin-producing Escherichia coli (STEC) strains are major zoonotic food-borne pathogens of public health importance. Although cattle are recognized as a major reservoir of STEC, these strains have been frequently isolated from the intestinal content of swine, therefore swine shed STEC in the feces. Shiga toxin genes were subtyped to assess public health implications of STEC. By subtyping the stx2 gene subtypes in swine we established the presence of the stx2e gene in 9 out of 82 stx2 positive samples. Furthermore, the zoonotically significant stx2a gene in 3 samples, which, although with a low prevalence, is of great importance for public health, enabling completion of the epidemiological picture of STEC in Serbia.